Use IR-spectroscopy in treatment oncological patients with bone metastasises by ¹⁵³Sm-oxabifor - Dikiy, N.P.; Krasnoselsky, N.V.; Bereznyak, E.P.; Grushka, A.V.; Medvedeva, E.P. (Вопросы атомной науки и техники, 2020)
Using infrared spectroscopy, we studied the character of intermolecular interactions in the samples blood plasma of oncological patients with bone metastases in the treatment of their modern β-emitter ¹⁵³Sm-oxabifor. The therapeutic dose of the ¹⁵³Sm-oxabifor was 1.0 mCi/kg of the patient’s body weight. Analysis of the IR spectra showed that already after the first course of palliative radionuclide therapy there is a tendency to balance the products of free radical nature and antioxidants, which indicates the effectiveness of the treatment. Molecular changes in the blood plasma of cancer patients with bone metastases registered using infrared spectroscopy are specific during palliative therapy. Методом ІЧ-спектроскопії вивчено характер міжмолекулярних взаємодій в зразках плазми крові онкологічних хворих з кістковими метастазами в процесі лікування їх сучасним β-випромінювачем ¹⁵³Sm-оксабіфором. Лікувальна доза препарату ¹⁵³Sm-оксабіфору становила 1,0 мКі/кг маси тіла хворого. Аналіз ІЧ-спектрів показав, що вже після першого курсу паліативної радіонуклідної терапії відзначається тенденція до збалансування продуктів вільнорадикальної природи і антиоксидантів, що свідчить про ефективність проведеного лікування. Зареєстровані за допомогою методу ІЧ-спектроскопії молекулярні зміни в плазмі крові онкологічних хворих з кістковими метастазами є специфічними під час проведення паліативної терапії. Методом ИК-спектроскопии изучен характер межмолекулярных взаимодействий в образцах плазмы крови онкологических больных с костными метастазами в процессе лечения их современным β-излучателем ¹⁵³Sm-оксабифора. Лечебная доза препарата ¹⁵³Sm-оксабифором составляла 1,0 мКи/кг массы тела больного. Анализ ИК-спектров показал, что уже после первого курса паллиативной радионуклидной терапии отмечается тенденция к сбалансированию продуктов свободнорадикальной природы и антиоксидантов, что свидетельствует об эффективности проводимого лечения. Зарегистрированные с помощью метода ИК-спектроскопии молекулярные изменения в плазме крови онкологических больных с костными метастазами являются специфическими в ходе проведения паллиативной терапии.